Harvest Time Optimization for Biomass Productivity and Combustion Quality of Tall Wheatgrass in a Semi‐Arid Mediterranean Environment - Recep Irfan Nazli; Mihrab Polat; Asiye Sena Cavdar; Veyis Tansi (GCB Bioenergy)
ABSTRACT Optimizing harvest time has a significant impact on biomass productivity and combustion quality, making it essential to produce sustainable solid biofuel from perennial grasses. This study was conducted to determine the optimum harvest time in tall wheatgrass for the production of solid biofuel in a semi‐arid Mediterranean environment by evaluating the effects of six different harvest times (November, January, March, May, July, and September) on biomass yield and combustion quality parameters over two growing seasons. Dry matter yield of the crop steadily increased from the November to May harvest, which approximately coincided with the end of the growing season, but then it was significantly reduced by both the July and September harvests. Additionally, the content of cell wall components (lignin, cellulose, and hemicellulose) and the lignin/holocellulose ratio gradually increased with the progression of maturity and senescence. In contrast, ash, moisture, and mineral (N, P, K, Ca, Mg, S, Si, Cl, Na, and Zn) contents tended to decrease from the May to September harvest. In this regard, the September harvest significantly improved combustion quality by reducing the contents of ash, mineral, and moisture, the risks of slagging, aerosol formation, and corrosion, and increasing the lignin content and lignin/holocellulose ratio, despite causing a 22% yield loss in comparison to the May harvest. These results suggest that the September harvest may be primarily preferred for the sustainable solid biofuel production from tall wheatgrass in the dry marginal lands of the Mediterranean region.